Factores de riesgos físicos, químicos, biológicos y ergonómicos a los que están expuestos el personal profesional de enfermería del Hospital Manuel Ygnacio Monteros-IESS - Coello Loaiza, Sandra Maribel (2015)
The present investigation was carried out to the professional nursing staff of the Hospital Manuel Ygnacio Monteros-IESS of the city of Loja, took a quantitative approach to descriptive type, and was raised identify the risk factors physical, chemical, ergonomic and biological to which they are exposed the professional staff of nursing, participated in the study 98 professional nurses, was applied as technical survey and the instrument was the questionnaire, the analysis is carried out based on the literature review; the results show that physical risks, the noises are represented with 82% caused by the continuous handling of monitors, intravenous pumps; 22% felt that there is poor lighting; the space is narrow to circular 50%; changes abrupt temperature 68%; with respect to chemical hazards, the nursing staff is continuously exposed to antiseptics and disinfectants such as: alcohol 94%, iodized alcohol 50 %, savlon 78%, chlorine 68%, virkon 66%; to surgical gases continuously due to the gas, which produces the electrocautery 26% and anesthetic gases the 24% in the areas of surgical center and obstetric center; in regard to biological hazards the results show that the nursing staff if you have suffered accidents with sharp material when preparing or administering medication a 66%; the biological fluids to those who are continuously exposed are the blood with the 90%, the urine in a 58%, a salivary secretions 52%; and with regard to the ergonomic hazards to which it is exposed the professional staff of nursing studied, the results reveal that do not apply body mechanics 12%, the prolonged posture which is standing with a 86 %, and the forced posture a 76%. Key words: Physical hazards, chemical hazards, biological hazards, ergonomic hazards.